Nucleolar Organizer Region (NORs) in pseudocarcinomatous hyperplasia and squamous cell carcinoma of the oral mucosa - Altemani, Albina Messias de Almeida Milani; Crespo , Agrício; Cardinalli, lzilda Aparecida; Norato, Denise (São Paulo Medical Journal, 1995)
Counts of nucleolar regions (NORs) demonstrated by a silver staining technique in paraffin sections, have been used to distinguish benign from malignant lesions. AgNORs were studied in 24 biopsies from oral cavity (5 cases of normal oral mucosa, 5 of pseudocarcinomatous hyperplasia and 14 of squamous cell carcinoma, subdivided according to degree of differentiation: 5 grade 1, 5 grade 2 and 4 grade 3) to find whether they were helpful in distinguishing pseudocarcinomatous hyperplasia due to chronic parasitic infections from squamous cell carcinoma. Two methods of counting AgNORs were used: (A) a simpler one which counts nucleolar clusters (AgNU) and satellite AgNORs and the other (B) counting all individual AgNORs, including those within AgNUs. In both methods the lowest mean values were observed for grade 3 carcinoma, while the highest belonged to grade 2 carcinoma. The simpler method (A) was the most useful because AgNU counts showed significant difference when pseudocarcinomatous hyperplasia was compared with grade 1 and 2 carcinomas, which are the most difficult to discriminate from it. However the overlapping of values render the technique of limited use in individual cases.